The International Conference on ASEAN 2019 (De Gruyter, 2019)
Since the establishment of ASEAN (Association of Southeast Asian Nations) as a regional organization in 1967, it has played a significant role most importantly related to regional affairs and has also given notable contribution to the international arena. Undisputedly, ASEAN has been successfully fostering good relations among its members since its foundation. After completing the first period of its vision of an integrated regional community (ASEAN Community 2015), ASEAN is now preparing for the launch of ASEAN Community Vision 2025, supported by ASEAN Connectivity 2025. As a study center focusing primarily and solely on ASEAN, in collaboration with the Directorate General of ASEAN Cooperation, Indonesian Ministry of Foreign Affairs, the Center of ASEAN Studies Andalas University, will be hosting the International Conference on ASEAN (IC-ASEAN) as a platform to evaluate past actions, to discuss present issues, and to provide an outlook for the future of ASEAN. Aims and Scope The International Conference on ASEAN (IC-ASEAN) is a multidisciplinary conference which covers a broad range of area. The sub theme will be divided into two large categories focusing on ASEAN Community 2015 and 2025 also ASEAN Connectivity 2025. The sub theme related to ASEAN Community will cover issues related to the three pillars (Political-security Community, Economic Community and Social-cultural Community). Meanwhile the ASEAN Connectivity sub theme will include issues within the key areas (Physical Connectivity, Institutional Connectivity and People-to-people Connectivity. ASEAN POLITICAL-SECURITY COMMUNITY Diplomacy High Politic Issues Traditional Security Issues Law and Legality Non-Traditional Security Issues Human Right ASEAN ECONOMIC COMMUNITY Free Mark